PENGARUH KUALITAS PERTEMANAN TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN QUR’AN HADITS DI KELAS X MAN 1 SUMEDANG - Miftah Fauzan, Jihdan; Saefudin, Dindin; Zaelani, Moh. Ichsan (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study aims to determine the effect of friendship quality on student learning motivation in the subject of Qur'an Hadith in class X MAN 1 Sumedang. This study is a correlational quantitative study using a survey method. The data collection techniques used were observation, interviews, documentation, and the distribution of questionnaires or surveys. The population in this study consisted of 104 students, with a sample of 26 students selected using simple random sampling. The results showed that the significance value (sig. = 0.001) < (0.05) and the t-count value was 3.923 compared to the t-table value of 2.056, which means that t-count > t-table. Therefore, it can be interpreted that variable X (quality of friendship) has a significant effect on variable Y (student learning motivation). The contribution of this influence is 39.1%, which is categorized as weak, while the remaining 60.9% is influenced by other factors. The benefit of this study is that it provides an understanding of the importance of friendship quality in building student learning motivation, which can be used as a reference for educators and schools in creating a good learning environment.